Behavioral pattern of a monopolar passive direct methanol fuel cell stack - Kim, Young-Jin; Bae, Byungchan; Scibioh, M. Aulice; Cho, EunAe; Ha, Heung Yong (ELSEVIER SCIENCE BV, 2006)
A passive, air-breathing, monopolar, liquid feed direct methanol fuel cell (DMFC) stack consisting of six unit cells with no external pump, fan or auxiliary devices to feed the reactants has been designed and fabricated for its possible employment as a portable power source. The configurations of the stack of monopolar passive feed DMFCs are different from those of bipolar active feed DMFCs and therefore its operational characteristics completely vary from the active ones. Our present investigation primarily focuses on understanding the unique behavioral patterns of monopolar stack under the influence of certain operating conditions, such as temperature, methanol concentration and reactants feeding methods. With passive reactants supply, the temperature of the stack and open circuit voltage (OCV) undergo changes over time due to a decrease in concentration of methanol in the reservoir as the reaction proceeds. Variations in performance and temperature of the stack are mainly influenced by the concentration of methanol. Continuous operation of the passive stack is influenced by the supply of methanol rather than air supply or water accumulation at the cathode. The monopolar stack made up of six unit cells exhibits a total power of 1000 mW (37 MW cm(-2)) with 4 M methanol under ambient conditions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: DMFC; CROSSOVER; PERFORMANCE; MEMBRANE; DIFFUSION; OPERATION; SYSTEM; POWER